Effect of adjuvant therapy with compound danshen drip pill on inflammatory factors and cardiac function after percutaneous coronary intervention for acute myocardial infarction: a systematic review and meta-analysis - Fan, Genhao; Liu, Menglin; Song, Huanhuan; Wang, Yongxia (Frontiers in Pharmacology, 2024)
The purpose of the study was to comprehensively evaluate efficacy and safety of CDDP in patients with AMI undergoing PCI. A computerised search was conducted on the CNKI, WF, VIP, CBM, PubMed, Embase, Web of Science, and Cochrane Library databases for RCTs of CDDP adjuvant therapy for AMI up to May 2023. STATA 17.0 was used to perform meta-analyses, sensitivity analyses, subgroup analyses, meta-regression, and publication bias assessments. TSA 0.9.5.10 Beta was used for trial sequential analysis (TSA). Evidence confidence of meta results was evaluated by GRADE (Grading of Recommendations Assessment, Development and Evaluation) according to the instructions. The results of the meta-analysis showed that CDDP combined with conventional western treatment (CWT) was superior to CWT in increasing LVEF and TCER and decreasing LVEDD, hs-CRP, IL-6 and TNF-α. The quality of evidence for TCER was moderate, LVEF, LVEDD, IL-6, and TNF-α were low. The TSA results showed that the total number of samples collected in this study met the requirements for meta-analysis and excluded the possibility of false positives, further confirming the efficacy of CDDP for the treatment of AMI undergoing PCI. Adjuvant treatment of AMI with CDDP has shown exciting and safe benefits in improving cardiac function and reducing inflammatory response in patients with AMI undergoing PCI, but the quality of some of the included studies was poor, and the results should be interpreted with caution until further confirmation by well-designed RCTs.